An optimised state‐of‐charge balance control strategy for distributed energy storage units in islanded DC microgrid. Issue 6 (24th December 2020) - Mi, Yang; Ma, Yuchen; Yu, Si; Cai, Pengcheng; Ji, Liang; Fu, Yang; Yue, Dong; Jin, Chi; Wang, Peng
Abstract: The optimised droop control method is proposed to achieve the state‐of‐charge (SoC) balance among parallel‐connected distributed energy storage units in islanded DC microgrid, which considers the difference of line impedance, initial state‐of‐charge values and capacities among distributed energy storage units. Since the droop control is the basic control strategy for load sharing in DC microgrid applications, however, the load sharing accuracy is degraded under conventional droop control method due to the unmatched line impedance in reality. Meanwhile, the initial state‐of‐charge values and capacities of each distributed energy storage unit are usually different. Hence, the state of charge for distributed energy storage units cannot be balanced. In order to prolong the lifetime of the distributed energy storage units and avoid the overuse of a certain distributed energy storage unit, the optimised droop control strategy based on sample and holder is designed, by modifying the droop coefficient adaptively, the accurate load sharing and balanced state of charge among distributed energy storage units are both obtained. Finally, the performance of the proposed control scheme is accessed through a series cases on technologies real‐time digital simulator (RTDS) and its effectiveness is verified.